Tax Avoidance, Mekanisme Bonus, Intangible Assets, dan Leverage terhadap Transfer Pricing - Nabilah Sajidah Hasna; Lesi Hartati; Mutiara Kemala Ratu (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2026)
The purpose of this study is to investigate transfer pricing policies in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 by examining tax reduction, bonus mechanisms, intangible assets, and leverage. The secondary data used in this study were obtained from the companies' annual financial statements. This data was analyzed using SPSS 26. The results of the study indicate that bonus mechanisms and tax avoidance do not affect transfer pricing. Conversely, intangible assets and leverage have a significant partial effect on transfer pricing. However, all four factors simultaneously have a substantial impact on transfer pricing. The independent variables are able to explain 59.8% of the variance in transfer pricing. Other factors not examined in this study influence the remaining portion.